Publication of data collection forms from NHLBI funded sickle cell disease implementation consortium (SCDIC) registry - Jeffrey A. Glassberg; Elizabeth A. Linton; Katrina Burson; Tabitha Hendershot; Joseph Telfair; Julie Kanter; Victor R. Gordeuk; Allison A. King; Cathy L. Melvin; Nirmish Shah; Jane S. Hankins; Axel Yannick Epié; et al. (Orphanet Journal of Rare Diseases, 2020)
Abstract Background Sickle cell disease (SCD) is an autosomal recessive blood disorder affecting approximately 100,000 Americans and 3.1 million people globally. The scarcity of relevant knowledge and experience with rare diseases creates a unique need for cooperation and infrastructure to overcome challenges in translating basic research advances into clinical advances. Despite registry initiatives in SCD, the unavailability of descriptions of the selection process and copies of final data collection tools, coupled with incomplete representation of the SCD population hampers further research progress. This manuscript describes the SCDIC (Sickle Cell Disease Implementation Consortium) Registry development and makes the SCDIC Registry baseline and first follow-up data collection forms available for other SCD research efforts. Results Study data on 2400 enrolled patients across eight sites was stored and managed using Research Electronic Data Capture (REDCap). Standardized data collection instruments, recruitment and enrollment were refined through consensus of consortium sites. Data points included measures taken from a variety of validated sources (PHENX, PROMIS and others). Surveys were directly administered by research staff and longitudinal follow-up was coordinated through the DCC. Appended registry forms track medical records, event-related patient invalidation, pregnancy, lab reporting, cardiopulmonary and renal functions. Conclusions The SCDIC Registry strives to provide an accurate, updated characterization of the adult and adolescent SCD population as well as standardized, validated data collecting tools to guide evidence-based research and practice.